GENOTOXIC AND CYTOTOXIC EFFECTS OF ORAL VANADYL SULPHATE - Shah, Syed Zubair Hussain; Rashid, Amir; Naveed, Abdul Khaliq; Khan, Saleem Ahmed; Jahan, Sarwat (Journal of Ayub Medical College Abbottabad, 2019)
Background: Vanadyl sulphate is available as herbal medicine against diabetes mellitus and body building supplement, over the counter worldwide. The available data on its safety is controversial and inadequate. The objective of this study was to analyse its safety in usual therapeutic dose range. Methods: It was an experimental study carried out at the Department of Biochemistry & Molecular Biology, Army Medical College, National University of Medical Sciences (NUMS), Rawalpindi, Pakistan, from Jun 2014 to Oct 2018. The study was carried out on 105 Sprague Dawley rats for a duration of 24 weeks. The animals were randomly distributed in three groups of 35 each. The group I rats were marked as control while rats of group II & III were administered vanadyl sulphate 0.06mg/day and 0.3mg/day respectively. Alanine amino transferase (ALT) and Malondialdehyde (MDA) were measured in serum while comet assay was performed on WBCs. Results: The plasma levels of ALT and MDA were significantly raised in group II and III subjects. Single cell gel electrophoresis (SCGE) / comet assay showed minimal tail moment in control group and increased tail moment in group II and III in a dose dependent manner which indicates dsDNA breaks. Conclusion: It was observed that vanadyl sulphate causes hepatocellular toxicity, oxidative stress and damage to the DNA in usual therapeutic/ supplemental doses. Due to hazardous effects, its use in humans as alternate medicine may be reviewed. Keywords: Vanadyl sulphate; Hepatotoxicity; Oxidative Stress; DNA Damage; Comet Assay